Does color matter? Molecular and ecological divergence in four sympatric color morphs of a coral reef fish. Issue 18 (3rd September 2020) - Gaither, Michelle R.; Coker, Darren J.; Greaves, Samuel; Sarigol, Fatih; Payet, Samuel D.; Chaidez, Veronica; Sinclair‐Taylor, Tane H.; DiBattista, Joseph D.; Berumen, Michael L.
Abstract: Non‐sex‐linked color polymorphism is common in animals and can be maintained in populations via balancing selection or, when under diversifying selection, can promote divergence. Despite their potential importance in ecological interactions and the evolution of biodiversity, their function and the mechanisms by which these polymorphisms are maintained are still poorly understood. Here, we combine field observations with life history and molecular data to compare four sympatric color morphs of the coral reef fish Paracirrhites forsteri (family Cirrhitidae) in the central Red Sea. Our findings verify that the color morphs are not sex‐limited, inhabit the same reefs, and do not show clear signs of avoidance or aggression among them. A barcoding approach based on 1, 276 bp of mitochondrial DNA could not differentiate the color morphs. However, when 36, 769 SNPs were considered, we found low but significant population structure. Focusing on 1, 121 F ST outliers, we recovered distinct population clusters that corresponded to shifts in allele frequencies with each color morph harboring unique alleles. Genetic divergence at these outlier loci is accompanied by differences in growth and marginal variation in microhabitat preference. Together, life history and molecular analysis suggest subtle divergence between the color morphs in this population, the causes for which remain elusive. Abstract : Despite their potential importance in ecological interactions and the evolution of biodiversity, non‐sex‐linked color polymorphism is poorly understood. Here, we investigated four sympatric color morphs of the coral reef fish Paracirrhites forsteri (family Cirrhitidae) in the central Red Sea and show that the color morphs inhabit the same reefs. While we could not differentiate between them using mtDNA, when we considered 36, 769 SNPs, we found low but significant population structure that corresponded to color morphology with accompanying differences in growth and marginal variation in microhabitat preference.